Synthesis and Properties of Flexible Polyurethane Using Ferric Catalyst for Hypopharyngeal Tissue Engineering - Shen, Zhisen (2015)
Biodegradable polyurethane is an ideal candidate material to fabricate tissue engineered hypopharynx from its good mechanical properties and biodegradability. We thus synthesized a hydrophilic polyurethane via reactions among polyethylene glycol (PEG), e-caprolactone (e-CL) and hexamethylene diisocyanate (HDI), and thrihydroxymethyl propane (TMP). The product possessed a fast degradability due to its good wettability and good mechanical parameters with the elongations at break (137 ± 10%) and tensile strength (4.73 ± 0.46 MPa), which will make it a good matrix material for soft tissue like hypopharynx. Its biological properties were evaluated via in vitro and in vivo tests. The results showed that this hydrophilic polyurethane material can support hypopharyngeal fibroblast growth and owned good degradability and low inflammatory reaction in subcutaneous implantation. It will be proposed as the scaffold for hypopharyngeal tissue engineering research in our future study.